Food Cost Control Strategy at Hyatt Regency Bali - Krisnayana, Gusti Ngurah Oka; Sumariati, I Dewa Ayu Rai; Mareni, Ni Ketut (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study was conducted to determine the causes of deviations in actual food costs from standard food costs set by management and food cost control strategies at Hyatt Regency Bali. This study uses primary and secondary data in the form of documentation and interviews with the cost control, purchasing and receiving departments. As for data analysis techniques, this study uses qualitative descriptive analysis techniques by comparing interview data between informants and the theory used. The results of this study indicate that there is a difference between standard food costs and actual food costs of 4% which is caused by suboptimal food purchasing and receiving procedures. The results of this study state that the food procurement procedure has been running, but when purchasing or receiving food in large quantities, the purchasing and receiving parties tend to pay less attention to the procedures set by the company, such as the purchasing department does not apply standard purchase specifications when making urgent food purchases, the receiving department tends to trust suppliers to calculate and weigh incoming goods themselves when goods arrive in large quantities.